Emergency Department Staff Attitudes Toward People Presenting in Chronic Pain: A Qualitative Study. Issue 11 (14th July 2015) - Gauntlett‐Gilbert, Jeremy; Rodham, Karen; Jordan, Abbie; Brook, Peter
Abstract: Objective: Patients who experience their nonmalignant chronic pain as intolerable sometimes present at Emergency Departments (EDs). However, as emergency medical services are set up to provide rapid treatment for acute injury or illness; there is potential for misunderstanding and disappointment. Literature on the topic of ED staff attitudes toward chronic pain patients is minimal, USA‐based and methodologically unsatisfying. We carried out an in‐depth, qualitative study identifying the attitudes and narratives of ED staff around people in chronic pain. Design: Focus groups with ED staff; qualitative analysis of the group transcripts. Setting: Regional trauma centre in the UK. Subjects: Three focus groups, 20 ED clinicians, mean ED experience 8.1 years. Results: The clinical challenge of treating patients in the ED stemmed from a mismatch between patients' needs and what the setting can deliver. Participants reported frustration with the system and with chronic pain patients' perceived inconsistencies and requirements. However, they also highlighted good practice and acknowledged their frustration around not being able to help this group. Conclusions: ED staff found people presenting at ED with chronic pain to be a challenging and frustrating population to treat. Staff was constrained by the fast‐paced nature of their jobs as well as the need to prioritise emergency cases, and so were unable to spend the time needed by chronic pain patients. This was seen as being bad for staff, and for the patient experience. Staff suggested that care could be improved by appropriate information, signposting and with time invested in communication with the patient.